Two-dose emtricitabine/tenofovir alafenamide plus bictegravir prophylaxis protects macaques against SHIV infection. (17th November 2020) - Bekerman, Elena; Cox, Stephanie; Babusis, Darius; Campigotto, Federico; Das, Moupali; Barouch, Dan H; Cihlar, Tomas; Callebaut, Christian
Abstract: Objectives: Current prophylaxis options for people at risk for HIV infection include two US FDA-approved daily pre-exposure prophylaxis (PrEP) regimens and guidelines for a 2-1-1 event-driven course specifically for men who have sex with men. Despite this, PrEP use rates remain suboptimal, and additional PrEP options may help to improve uptake among diverse populations. Here, we evaluated protective efficacy of two-dose PrEP and two-dose postexposure prophylaxis (PEP) schedules with emtricitabine (FTC)/tenofovir alafenamide (TAF) with or without bictegravir (BIC) in an SHIV macaque model. Methods: Macaques received one oral dose of 200 mg emtricitabine, 25 mg tenofovir alafenamide and 25-100 mg of bictegravir to establish pharmacokinetic profiles of each drug either in the plasma or the peripheral blood mononuclear cells. Protective efficacy of multiple two-dose PrEP and PEP schedules with FTC/TAF with or without bictegravir was then assessed in two repeat low-dose rectal SHIV challenge studies. Results: The data revealed over 95% per-exposure risk reduction with FTC/TAF PrEP initiated 2 h before the exposure, but a loss of significant protection with treatment initiation postexposure. In contrast, FTC/TAF plus BIC offered complete protection as PrEP and greater than 80% per-exposure risk reduction with treatment initiation up to 24 h postexposure. Conclusions: Together, these results demonstrate that two-dose schedules can protect macaques against SHIV acquisition and highlight the protective advantage of adding the integrase inhibitor bictegravir to the reverse transcriptase inhibitors emtricitabine and tenofovir alafenamide as part of event-driven prophylaxis.